Palmitate-Induced Insulin Hypersecretion and Later Secretory Decline Associated with Changes in Protein Expression Patterns in Human Pancreatic Islets - Groebe, Karlfried; Cen, Jing; Schvartz, Domitille; Sargsyan, Ernest; Chowdhury, Azazul; Roomp, Kirsten; Schneider, Reinhard; Alderborn, Anders; Sanchez, Jean-Charles; Bergsten, Peter (Journal of proteome research, 2018)
In obese children with high circulating concentrations of free fatty acid palmitate, we have observed that insulin levels at fasting and in response to a glucose challenge were several times higher than in obese children with low concentrations of the fatty acid as well as in lean controls. Declining and even insufficient insulin levels were observed in obese adolescents with high levels of the fatty acid. In isolated human islets exposed to palmitate we have observed insulin hypersecretion after 2 days exposure. In contrast, insulin secretion from the islets was reduced after 7 days culture in the presence of the fatty acid. This study aims at identifying islet-related biological events potentially linked with the observed insulin hypersecretion and later secretory decline in these obese children and adolescents using the islet model. We analyzed protein expression data obtained from human islets exposed to elevated palmitate levels for 2 and 7 days by an improved methodology for statistical analysis of differentially expressed proteins. Protein profiling of islet samples by liquid chromatography–tandem mass spectrometry identified 115 differentially expressed proteins (DEPs). Several DEPs including sorcin were associated with increased glucose-stimulated insulin secretion in islets after 2 days of exposure to palmitate. Similarly, several metabolic pathways including altered protein degradation, increased autophagy, altered redox condition, and hampered insulin processing were coupled to the functional impairment of islets after 7 days of culture in the presence of palmitate. Such biological events, once validated in the islets, may give rise to novel treatment strategies aiming at normalizing insulin levels in obese children with high palmitate levels, which may reduce or even prevent obesity-related type 2 diabetes mellitus.